Answer:
Not a function because it does not pass the Vertical Line Test.
Answer:
x+7
Step-by-step explanation:
7/y-?/y=x/y
?=x+7
Sorry, I wish I could elaborate more but I can't...
Answer:
![\frac{4}{3}{\sqrt3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%7B%5Csqrt3%7D)
Step-by-step explanation:
The question seem incomplete;
The full question is
<em>Which expression is equivalent to 4√6/3√2
</em>
<em></em>
Given
4√6/3√2
Required
Find equivalent
![4\sqrt6/3\sqrt2](https://tex.z-dn.net/?f=4%5Csqrt6%2F3%5Csqrt2)
Rewrite Expression
![\frac{4\sqrt6}{3\sqrt2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%5Csqrt6%7D%7B3%5Csqrt2%7D)
Expand the above expression
![\frac{4\ *\ \sqrt6}{3\ * \ \sqrt2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%5C%20%2A%5C%20%5Csqrt6%7D%7B3%5C%20%2A%20%5C%20%5Csqrt2%7D)
Further split the fraction
![\frac{4}{3}\ *\ \frac{\sqrt6}{\sqrt2}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%5C%20%2A%5C%20%5Cfrac%7B%5Csqrt6%7D%7B%5Csqrt2%7D)
Using rule of surds;
![\frac{\sqrt a}{\sqrt b} = \sqrt{\frac{a}{b}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%20a%7D%7B%5Csqrt%20b%7D%20%3D%20%5Csqrt%7B%5Cfrac%7Ba%7D%7Bb%7D%7D)
So, the above expression becomes
![\frac{4}{3}\ *\ \sqrt{\frac{6}{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%5C%20%2A%5C%20%5Csqrt%7B%5Cfrac%7B6%7D%7B2%7D%7D)
![\frac{4}{3}\ *\ {\sqrt3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%5C%20%2A%5C%20%7B%5Csqrt3%7D)
![\frac{4}{3}{\sqrt3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%7B%5Csqrt3%7D)
At this stage, the expression cannot be further simplified;
Hence, 4√6/3√2 = ![\frac{4}{3}{\sqrt3}](https://tex.z-dn.net/?f=%5Cfrac%7B4%7D%7B3%7D%7B%5Csqrt3%7D)
Answer:
21
Step-by-step explanation:
The sum of degrees in a triangle is 180, so we have:
3x+100+x-4=180
add 4 on both sides
3x+100+x=184
subtract 100 on both sides
3x+x=84
Combine like terms
4x=84
84/4 = 21
(btw i'm actually 10 years old 0_0)